Mobility Disability and Exercise: Health Outcomes of an Accessible Community-Based Center - Morgan, Kerri A.; Taylor, Kelly L.; Walker, Carla Wilson; Tucker, Susan; Dashner, Jessica L.; Hollingsworth, Holly (Frontiers in Rehabilitation Sciences, 2022)
Objective: The purpose of this study was to determine how support and guidance provided by trained professionals during a 12-week, community-based transition exercise program, impact health outcomes and continued engagement in physical activity for persons with a mobility disability (PwMD). Design: A single arm pre-post design was used. Setting: Accessible community-based health and wellness center Participants: The study included 244 PwMD using a mobility device. Interventions: Participants completed a 12-week transition exercise program provided through an accessible community facility that provided education and support to complete endurance and strength related exercises as well as programming to encourage transition to self-directed engagement in exercise. Main Outcome Measures: Bodyweight, BMI, pain, perceived exertion, speed, and distance during cardiovascular fitness testing, and strength were measured pre and post exercise program. The number of participants that signed up for a monthly membership after the program was also monitored. Results: For the total group, average pain reported over previous 30 days decreased significantly (p<0.01), current daily pain decreased significantly (p<0.05), perceived exertion at the end of the 9-minute endurance test decreased significantly (p<0.05), and the four upper extremity strength exercises showed large, significant strength gains (p<0.01) after the program. There was no significant change in bodyweight, BMI, or speed and distance completed during endurance testing. At the completion of the program, seventy-six percent of participants enrolled in a monthly membership at the facility with the intentions to continue to exercise regularly. Conclusions: This study provides evidence that an accessible community-based exercise program, with a transitional component supported by trained professionals, can support the exercise goals of PwMD and improve strength, decrease pain, and may promote regular exercise adoption for PwMD.